Implementation of Differentiated Learning in Kurikulum Merdeka Belajar (Independent Learning Curriculum) at Islamic Elementary Schools - Lutfa, Asna; Asna Lutfa; Anggun Pastika Sandi; Amaira Utami; Ahmad Fahrijal (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The aim of this research is to find out first, the implementation of differentiated learning in the independent curriculum; second, strategies for implementing differentiated learning; third, challenges in implementing differentiated learning. The research method used is a descriptive analytical method with a qualitative approach. The subjects in the research were Madrasah Ibtidaiyah (Islamic Elementary School) in the DKI Jakarta Province Region which implemented the Merdeka Curriculum. The data collection techniques used were observation, interviews and documentation as well as descriptive data analysis using data reduction and data triangulation. Testing the validity of the data is carried out through source triangulation and technical triangulation. The results of this research show that first, madrasahs have various internal policies, including special approaches including superior program tests, strengthening Pancasila values, introducing and familiarizing with literacy to support the implementation of the Independent Curriculum, in the implementation the teachers already understand differentiated learning. Second, the strategies applied in differentiated learning include carrying out initial assessments, grouping students, taking various approaches to accommodate the diversity of student profiles, preparing media and teaching materials that are not monotonous, and carrying out final assessments. Third, the challenges in implementing differentiated learning are that teachers still experience several obstacles, including understanding the characters of different students; adapting material that can be integrated into the discussion; improving learning media skills; determine students' talents, abilities and interests; inadequate media and infrastructure; limited time in implementing differentiated learning; students are difficult to control and there are still some who cannot read. The suggestions in this research require special assistance for teachers in madrasas; the need for Islamic Schools to collaborate with driving teachers, lecturers, researchers, the community, student parents and stakeholders involved; Madrasah heads need to take part in supervising some of the facilities and infrastructure needed by teachers.